APPLICATION OF ISLAMIC VALUES TO SMEs BUSINESS YOTTA DRINK PRODUCTS IN MAKASSAR - Syarifuddin, Syarifuddin; Wahyuni, Sri (Jurnal Iqtisaduna, 2019)
SMEs business have a very important role in Indonesia’s economic development and growth. The contribution of SMEs to Indonesia’s Gross Domestic Product (GDP) is 60.64% and absorbs a workforce of 97%, many of which have business management oriented to Islamic values but there are still those who violate their implementation. This study aims to find out about Islamic values which consist of halalness, honesty, quality of service, friendliness. in micro, small and medium enterprises (SMEs) especially in beverage products. The application of good Islamic values will create harmony in terms of Islamic business management. With this harmony in business, it will improve performance and productivity that is good for business people. This study analyzes the role of Islamic values on the management of SMEs performance in Beverage Products. This type of research uses descriptive qualitative research methods, by conducting observations directly to the publisher and interviews with employees, managers and the surrounding community, Technical Data analysis is done by reducing data, presenting data, and drawing conclusions. The results of this study indicate that Islamic values have a positive effect on the performance of SMEs Yotta in the city of Makassar.